2021
DOI: 10.1093/eurheartj/ehab724.0915
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and long-term outcomes of palliative inotropes in ischemic and non-ischemic cardiomyopathy

Abstract: Background Palliative inotropes are frequently utilized for symptom management in patients with end stage heart failure who are unable to undergo durable advanced heart failure therapies. With the advent of improved medical management and early intervention, palliative inotropes may allow for improved patient outcomes than seen previously. In this study, we aim to investigate the survival and outcomes of palliative inotrope therapy and its impacts on ischemic versus non-ischemic cardiomyopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Specifically, the supply of dobutamine has been limited due to manufacturing challenges and its increased demand has forced providers and hospitals to search for other alternative vasoactive drugs. Studies have found no significant difference in survival, complications, and outcomes of patients on milrinone or dobutamine with ischemic or nonischemic cardiomyopathies [32]. Therefore, these factors may play a more substantial role in choosing the ideal inotrope, particularly considering less profitability for many home health agencies.…”
Section: Inotrope Therapy In Palliative Care Settingsmentioning
confidence: 99%
“…Specifically, the supply of dobutamine has been limited due to manufacturing challenges and its increased demand has forced providers and hospitals to search for other alternative vasoactive drugs. Studies have found no significant difference in survival, complications, and outcomes of patients on milrinone or dobutamine with ischemic or nonischemic cardiomyopathies [32]. Therefore, these factors may play a more substantial role in choosing the ideal inotrope, particularly considering less profitability for many home health agencies.…”
Section: Inotrope Therapy In Palliative Care Settingsmentioning
confidence: 99%